Kraus' recreation and leisure in modern society - Hurd, Amy R.; Mainieri, Tracy; Anderson, Denise M. 1970- (Jones & Bartlett Learning, 2023)
"Kraus' Recreation and Leisure in Modern Society provides a detailed introduction to the history, developments, and current trends in leisure studies"--